Unified Mechanism Explanation of Anomalous Phenomena in Fluid Mechanics Based on the Unified Complex System Theory - Cui, Weicheng (European Journal of Applied Sciences, 2026)
The ten classic anomalous phenomena in aerodynamics and fluid mechanics have long been plagued by persistent dilemmas such as disconnection between theoretical predictions and experimental observations as well as the failure of global prediction, which restrict the disciplinary development of the field. Established on material monism and passive dynamics, the traditional theoretical system lacks the mechanisms of endogenous active force, multiscale emergence, and mind–ether dual ontological coupling. Moreover, the Navier–Stokes (NS) equations exhibit a narrow scope of application, suffering from sharp accuracy degradation and theoretical invalidation under complex operating conditions characterized by strong nonlinearity and multiscale coupling. Based on the Unified Complex System Theory and Bohmian mechanics, this paper constructs a global unified wave field framework and reconstructs the dynamic equations from the perspective of dual ontology, thereby providing a unified mechanistic interpretation for anomalous fluid phenomena. The research reveals that fluid anomalies originate from the combined effects of microscopic particle coupling, modulation of endogenous active forces, multiscale wave coherence, and nonequilibrium transition. It is demonstrated that the NS equations merely serve as a degenerate approximate model derived from the unified wave equation. The proposed new model bridges scales from the micro to the macroscale, offering a unified theoretical pathway for disciplinary theoretical innovation as well as engineering applications in aerospace, hydraulic engineering and related fields.